Biventricular tissue tracking demonstrating associations between left ventricular myocardial extracellular volume, pulmonary artery pressure, and reduced right ventricular ejection fraction in patients with systemic lupus erythematosus using cardiovascular MRI. Issue 3 (March 2020) - Wu, R.; Shi, R.Y.; An, D.A.L.; Chen, B.H.; Jiang, M.; Bacyinski, A.; Han, T.T.; Deen, J.M.; Kaddurah, H.; Hu, J.; Xu, J.R.; Wu, L.M.
Abstract : AIM: To investigate the feasibility and prognostic value of biventricular strain analysis for patients with systemic lupus erythematosus (SLE) and relationship to left ventricular (LV) myocardial fibrosis, pulmonary hypertension (PAH), and right ventricular (RV) ejection fraction (RVEF). MATERIALS AND METHODS: A total of 50 SLE patients (47 women; 34.4±12 years) and 15 controls (13 women; 32.9±8.6 years) were imaged via echocardiography and a 3 T magnetic resonance imaging (MRI). Pulmonary artery systolic pressure (sPAP) was assessed using echocardiography. Biventricular global circumferential strain (GCS), global longitudinal strain (GLS), global circumferential strain rate (GCSR), and global longitudinal strain rate (GLSR) as well as LV myocardial extracellular volume (ECV) were derived for each subject. RESULTS: Elevated LV ECV was significantly associated with LV GCS (beta –0.428, p= 0.000), GLS (beta 0.404, p= 0.000), GCSR (beta –0.350, p= 0.006), GLSR (beta –0.445, p= 0.000) and RV GCS (beta –0.373, p= 0.000), and the presence of reduced RVEF was significantly associated with LV GCS (beta –0.338, p= 0.002), GLS (beta –0.465, p= 0.000) and RV GCS (beta –0.465, p= 0.000). Raised sPAP was significantly associated with RV GLS (beta 0.445, p= 0.000) and GCSR (beta –0.387, p= 0.001). Moreover, there were significantly correlations between LV and RV strain and strain rate. CONCLUSIONS: Biventricular strain analysis may be a better prognostic tool for patients with SLE as it allows greater comprehensive analysis and more definitive treatment planning compared to separate assessment of LV or RV contractility. Highlights: Biventricular circumferential and longitudinal strain and strain rate parameters were reduced in SLE patients. LV GCS, GLS and RV GCS was not only associated with LV ECV but also RVEF. There were significantly correlations between LV and RV strain and strain rate.